EXPERIENCE OF APPLICATION OF MODERN TEACHING METHODS IN THE TRAINING OF SPECIALISTS OF SPECIALTY 193 «GEODESY AND LAND MANAGEMENT» IN THE ODESSA STATE ACADEMY OF CIVIL ENGINEERING AND ARCHITECTURE - Константинова, Елена; Колосюк, Анатолий; Стадников, Владимир; Стадникова, Наталия; Колыханин, Сергей (SWorldJournal, 2021)
The article analyzes modern teaching methods, as well as the introduction into the educational process of information and communication technologies, which should be used in the training of highly qualified specialists in the specialty 193 «Geodesy and L